Menghayati Asta Aiswarya Sebagai Kemahakuasaan Sang Hyang Widhi - Ni Putu Ayudya Putri; Nitya Yuli Pratistha (Pramana: Jurnal Hasil Penelitian, 2023)
Aiswarya is the form and nature of Ida Sang Hyang Widhi Wasa's omnipotence, both temporal and noetic, consisting of eight kinds of power, so that Aiswarya is also called Asta Aiswarya. Etymologically, asta aiswarya comes from the word